The Role of miR-640: A Potential Suppressor in Breast Cancer via Wnt7b/β-catenin Signaling Pathway - Tang, Chun; Wang, Xuehui; Ji, Changle; Zheng, Wenfang; Yu, Yunhe; Deng, Xiaochong; Zhou, Xiqian; Fang, Lin (Frontiers in Oncology, 2021)
In this study, we demonstrated that miR-640 is significantly downregulated in breast cancer (BC) tissues and cell lines. Overexpression of miR-640 inhibited the proliferation and migration of BC in vitro and in vivo, while depletion of miR-640 exhibited the opposite effect. Importantly, miR-640 could directly target Wnt7b, thereby regulating Wnt/β-catenin signaling pathway in BC. In conclusion, miR-640/ Wnt7b suppresses BC cells tumorigenesis via Wnt/β-catenin signaling pathway, which might be novel targets for BC targeted therapy.